Evaluating Impact of Empagliflozin on Lipid Profile of Patients of Type 2 Diabetes Mellitus - Nauman Wazir; Shafqat Ur Rehman (Gandhara University, 2022)
OBJECTIVES: To assess the effect of two doses, i.e., 10 mg and 25 mg of empagliflozin, on the lipid profile of patients with type 2 diabetes mellitus (T2DM) with suboptimal glycemic control on maximal doses of metformin and sitagliptin. METHODOLOGY: The study design was a randomized, open-label clinical trial. Fifty-nine adult patients of T2DM who were already on 2000 mg of Metformin and 100 mg of Sitagliptin and were having suboptimal glycaemic control (HBA1C > 7% <12%) were randomly allocated in 1:1 ratio to two groups, one group receiving 10 mg (Group A) and the other group receiving 25 mg of Empagliflozin (Group B) as an additional treatment. Fasting lipid profiles, including total cholesterol (TC), low-density cholesterol (LDL-C), high-density cholesterol (HDL-C) and triglycerides (TG), were taken before and 12 weeks after the addition of empagliflozin in both the groups.   RESULTS:   Total patients in group A were 31, and their mean age was 51.48±4.29 years. In group B, there were 28 patients, whose mean age was 52.39 ± 5.20 years. There was an increase in TC, LDL-C and HDL-C and a reduction of TG in both the groups after treatment with empagliflozin, but it was not statistically significant (p > 0.05). CONCLUSION: Both doses of Empagliflozin (10 and 25 mg) modestly elevates total cholesterol, LDL-C and HDL-C and modestly reduce triglyceride levels in T2DM patients, but the change is not statistically significant. KEYWORDS: Empagliflozin, Type 2 diabetes mellitus, Total cholesterol, Low-density cholesterol, High-density cholesterol, Triglycerides